1996
DOI: 10.1111/j.1600-0447.1996.tb09842.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Dhat syndrome’ : a culturally determined symptom of depression?

Abstract: The status of the 'Dhat syndrome' is called into question by the results of an epidemiological study of men attending general medical clinics in Lahore. The Dhat complaint was reported by 30% of men attending medical clinics, and to an equal extent by patients with 'functional' and 'organic' diagnoses. It was strongly associated with depressed mood, fatigue symptoms, and a DSM-III-R diagnosis of depression. It is argued that the Dhat complaint should be primarily regarded not as the focus of a culture-bound sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…However, the complaint of Dhat syndrome is not confined to Hindus, but is widespread among all communities of the Indian subcontinent. It has been reported among Sikhs in Punjab, Buddhists in Sri Lanka and Muslims in Pakistan (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the complaint of Dhat syndrome is not confined to Hindus, but is widespread among all communities of the Indian subcontinent. It has been reported among Sikhs in Punjab, Buddhists in Sri Lanka and Muslims in Pakistan (4).…”
Section: Introductionmentioning
confidence: 99%
“…16 The prominence of concern about semen discharge was also found in a recent community-based study among 2,084 men aged 18-35 in Orissa, where 27 per cent reported experience of semen discharge,2 l and among 11 per cent of 1,279 married slum dwellers in Mumbai in the two months prior to interview. 23 The Lahore study found that reported semen loss in urine was significantly associated with feelings of tiredness, weakness, difficulties in getting a complete erection and a burning sensation while urinating.…”
Section: Discussionmentioning
confidence: 72%
“…However, cultural formulations of sexual presentations in clinical work must be viewed in the context of other disorders that may be presenting. For example, authors have commented on the role of dhat as a somatic presentation in depressive illness (Mumford 1996). Here, cultural background is understood to be shaping the particular mode of presentation of the patient experiencing distress, rather than causing the disorder itself -an example of pathoplastic influences.…”
Section: Box 2 Sex Positivity and Sex Negativitymentioning
confidence: 99%